STOP BULLYING DAN ETIKA BERKOMUNIKASI - Syamsinah Sirait; Japina, Henky; Helmina Simanjuntak; Saria Sinaga; Heni Widia; Miftah Ar Razy (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The community service program entitled “Stop Bullying and Communication Ethics” was implemented at MIS Islamiyah, Padang Sari Village, Tinggi Raja District, Asahan Regency. This activity aimed to raise awareness among elementary school students about the dangers of bullying and the importance of applying ethical communication in daily interactions. The program adopted a participatory, educational, and contextual approach tailored to the students' developmental stages and needs. Implementation methods included interactive counseling, communication training, case simulations, and self-reflection activities, all designed to be engaging and applicable. Evaluation results indicated a significant improvement in students’ understanding of bullying definitions, types, negative impacts, and their ability to communicate respectfully and act as change agents within the school environment. The program also contributed to character education by emphasizing affective learning that connects with students’ personal experiences. Teachers appreciated the initiative, recognizing its effectiveness in fostering moral values through consistent educational efforts. Thus, this program can be replicated in other schools as a meaningful contribution to creating a safe, child-friendly, and value-based learning environment.